Pantekostalisme dalam Studi Agama: Merekonstruksi Sejarah Sosio-Intelektual di Indonesia - Elia Tambunan; MC Reonald Debataraja (DIEGESIS: Jurnal Teologi Kharismatika, 2024)
Some say that there is no Pentecostal theology, there is only biblical theology by previous academics, that is the main problem in this article. According to the author, the argument built on the framework and work of postcolonial studies epistemology actually reveals things related to Pantecost in Indonesia (including theology) for the emergence of something distinctive, local, and original, which is then named Pantecostalism as a technical umbrella term. So that, this article is not the same as the previous researcher. This qualitative research paper is a social history approach with a source analysis method. We collected apart from primary, empirical, observational, interview, as well as literature studies, whether it is by academics working in the Pentecostal field including social media on various platforms, website pages or non-Pantecostal but as a secondary source for the sake of building the solidity of the decipherment of the writing. This paper presents the findings of a new intellectual orientation on Pantecostal studies in Indonesia that should not be equated with studying global Pentecostalism, because Pantecostalism, although it has a historicality from a socio-intellectual perspective, has its own distinction so that it is appropriate to be included as an inherent part of the study of religion. Keywords: Indonesia; pantecostalism; socio-intellectual; study of religionAbstrak Tak sedikit yang mengatakan, tidak ada teologi Pantekosta, yang ada ialah teologi alkitabiah saja oleh para akademisi sebelumnya, itulah masalah utama dalam tulisan ini. Oleh penulis, argumentasi yang dibangun berdasarkan kerangka pikir dan kerja epistemologis postcolonial studies justru menampakkan hal-hal sekaitan dengan Pantekosta di Indonesia (termasuk teologi) demi munculnya sesuatu hal yang khas, yang lokal, dan yang asali, yang kemudian dinamai dengan Pantekostalisme sebagai payung istilah secara teknis. Sehingga, tulisan ini tidak sama dengan peneliti sebelumnya. Tulisan penelitian kualitatif ini pendekatan sejarah sosial dengan metode analisis sumber. Kami mengumpulkan data selain dari sumber primer, empiris, observasi, wawancara, juga dengan kajian literatur, apakah itu oleh akademisi yang bekerja di ladang Pantekosta termasuk media sosial berbagai platform, laman website maupun yang bukan Pantekosta namun sifatnya sebagai sumber sekunder demi terbangunnya soliditas uraian tulisan. Tulisan ini menampilkan temuan kebaruan orientasi intelektual terkait studi Pantekosta di Indonesia yang tidak boleh, tidak perlu disama-samakan dengan studi global Pentekostalisme karena Pantekostalisme meskipun memiliki pertalian historisitas dari sisi sosio-intelektual tetapi memiliki distingsi tersendiri sehingga tepat dimasukkan sebagai bagian inheren studi agama.Kata-Kata Kunci: Indonesia; pantekostalisme; sosio-intelektual; studi agama